Drugs in perspective - Fields, Richard; Fields, Richard (Madison, Wis. : Brown & Benchmark, 1995)
This textbook focuses on the effects of substance abuse on the individual and their family. It describes treatment and prevention techniques, outlines self-esteem and shame as factors in drug abuse and gives resource lists for available treatment programmes.
Rev. ed. of: Drugs and alcohol in perspective. c1992.
Includes bibliographical references and index.
Keywords: Drug abuse; Alcoholism; Drug abuse -- Prevention; Alcoholism -- Prevention; Drug abuse -- Treatment; Alcoholism -- Treatment